ANALISIS PEMBERDAYAAN GENDER DI PROVINSI SUMATERA BARAT - Rita Diana (Jurnal Kependudukan Indonesia, 2018)
The issue of women empowerment has been a critical development agenda, both in national dan international level. However, it would be difficult for women to be empowered if gender inequality still exists in essential aspects in development processes. This article aims to find out regencies/municipalities with high gender inequality in West Sumatera Province. This study employed a biplot method to analyze the 2015 Gender Empowerment Index data. Such method categorized regencies and municipalities in West Sumatra into three groups based on the components of gender empowerment. Of the three groups, the first group has prominent characteristics regarding their gender inequality that shown from high gender imbalances concerning women and men as professionals, managers, administrators and technicians and representation in parliament. Meanwhile, the second group features regions with a medium level of women’s contribution to income and women’s representation in parliament. Furthermore, the third group is attributed to a high proportion of women in parliament. The results from biplot method analysis show of 99.94% and STRESS score of 15.98%. These values indicate that the results are quite similar to the real condition.